2016
DOI: 10.1007/s12035-016-9726-4
|View full text |Cite
|
Sign up to set email alerts
|

Directed Differentiation of Dopamine-Secreting Cells from Nurr1/GPX1 Expressing Murine Embryonic Stem Cells Cultured on Matrigel-Coated PCL Scaffolds

Abstract: Parkinson's disease (PD) is a progressive neurological disorder characterized by a large number of motor and non-motor features and is known as the second most common neurodegenerative disorder after Alzheimer's disease. The hallmark pathology of PD is the damage and death of dopamine-producing neurons in the substantia-nigra of midbrain. Intrastriatal transplants of fetal mesencephalon derived DAergic neurons have provided proof-of-principle for the cell replacement strategy and have demonstrated reinnervatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…18-20 Although Matrigel has been demonstrated as an effective CNS-related cell carrier, it cannot be employed for clinical usage due to its unknown growth factor composition and murine sarcoma origins. 21-23 Therefore, there is an unmet need to develop other component-defined hydrogel systems to support hiPSC-NPCs and to improve the controllability. A number of attempts have been made to develop modified hyaluronic acid, agarose, alginate, or peptides-based hydrogel materials for hiPSC encapsulation.…”
Section: Introductionmentioning
confidence: 99%
“…18-20 Although Matrigel has been demonstrated as an effective CNS-related cell carrier, it cannot be employed for clinical usage due to its unknown growth factor composition and murine sarcoma origins. 21-23 Therefore, there is an unmet need to develop other component-defined hydrogel systems to support hiPSC-NPCs and to improve the controllability. A number of attempts have been made to develop modified hyaluronic acid, agarose, alginate, or peptides-based hydrogel materials for hiPSC encapsulation.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the Fmoc‐SAPs hydrogels are biocompatible in vivo and are utilized in neural grafts of intact brains . Terraf et al generated the mouse embryonic stem (mES) R1 cell line for the co‐expression of nuclear receptor‐related 1 protein (Nurr1) and GPX‐1. Poly‐ε‐caprolactone (PCL)/Matrigel nanofibrous scaffolds were used to establish the 3D environment .…”
Section: Supportive Materials In the Disease Modeling Of Neurologicalmentioning
confidence: 99%
“…Terraf et al generated the mouse embryonic stem (mES) R1 cell line for the co‐expression of nuclear receptor‐related 1 protein (Nurr1) and GPX‐1. Poly‐ε‐caprolactone (PCL)/Matrigel nanofibrous scaffolds were used to establish the 3D environment . The biocompatible nanofibrous scaffolds were fabricated by weaving the PCL solution with aluminum foil and were coated with gold .…”
Section: Supportive Materials In the Disease Modeling Of Neurologicalmentioning
confidence: 99%
See 2 more Smart Citations